Deep Learning Versus Surface Learning In Teaching English In Algerian Higher Education - Amara, Naimi (Université de M'sila, 2020)
This article tries to shed lights on the main differences between deep learning and surface learning at Higher Education (HE).In many Algerian English departments, surface learning characterises the tecahing-learning schene.Memorisation and little academic writing are preventing students from developing thier intellectual capacities. Deep learning is fostered by encouraging students to take a critical view of the subject and by giving them access to the tools to do this. Students often do not know what it is they do not know and therefore need to have a dialogue with their peers and with the tutor to help them understand. Teachers therefore, need to be plan well and need to try new ideas to cater for their students’ needs and differences. Teaching is a highly complex task to be accomplishedas ; it necissiates a good management of students and teaching materilas. Reflection on one’s teaching experience is more than required; as it enables teachers to improve the quality of thier courses and meet the students’ increasing needs.Thus,deep learning should be encouraged by our institutions and surface learning should be fought by all means to put an end to old bad learning-teaching habbits.
Keywords: collobarative learning ,deep learning, higher education, motivation. surface learning